(untitled) (Fiep Bulletin - online, 2016)
The objective of this study was to relate the level of physical activity with the obese and the risk of contracting diseases coronary arterio of employees of the campus Torquato Neto UESPI. We conducted a cross-sectional study that included 30 employees aged 20 and 60, who were not undergoing neuro-orthopedic rehabilitation in the city of Teresina - PI. Using the International Physical Activity Questionnaire (IPAQ) short version evaluated the level of physical activity. Anthropometric assessments was verified BMI, waist circumference and health levels was measured blood pressure and heart rate. Data processing and statistical analysis were performed using the SPSS software, version 18.0. We used descriptive statistics, as well as prevalence ratio (PR) and 95% confidence interval (95% CI) to analyze the level of relationship of physical activity and health. The significance criterion was 5%. Women constituted 53.3% of the study population and men 46.7%. The result was that 46.7% of employees practice activities irregularly compared to health shows that 53.3% are with normal body mass, 46.7% with normal blood pressure and 63.3% with waist circumference normal. Thus concluding that the study showed no significant difference between Very active / active and active Irregularly possibly the sample was small and the heterogeneity have been great. What does not fail to highlight the importance of regular practice of physical activity for the prevention of diseases coronary arterio.